Crystallization and preliminary X-ray crystallographic analysis of importin-alpha from Neurospora crassa - Bernardes, Natalia E. [UNESP]; Takeda, Agnes A. S. [UNESP]; Freitas, Fernanda Zanolli [UNESP]; Bertolini, Maria Celia [UNESP]; Fontes, Marcos R. M. [UNESP] (Wiley-Blackwell, 2014)
Importin-alpha recognizes cargo proteins that contain classical nuclear localization sequences (NLS) and, in complex with importin-beta, is able to translocate nuclear proteins through the nuclear pore complex. The filamentous fungus Neurospora crassa is a well studied organism that has been widely used as a model organism for fundamental aspects of eukaryotic biology, and is important for understanding the specific mechanisms of protein transport to the cell nucleus. In this work, the crystallization and preliminary X-ray diffraction analysis of importin-alpha from N. crassa (IMP alpha-Nc) complexed with a classical NLS peptide (SV40 NLS) are reported. IMP alpha-Nc-SV40 NLS crystals diffracted X-rays to 2.0 angstrom resolution and the structure was solved by molecular-replacement techniques, leading to a monomeric structure. The observation of the electron-density map indicated the presence of SV40 NLSs interacting at both the minor and major NLS-binding sites of the protein.